Drivers of Parasitoid Wasps' Community Composition in Cacao Agroforestry Practice in Bahia State, Brazil - Sperber, Carlos Frankl; Azevedo, Celso Oliveira; Muscardi, Dalana Campos; Szinwelski, Neucir; Almeida, Sabrina (IntechOpen, 2012)
None